SYNTHESIS OF 1,9-BIS [1-PHENYL-3-METHYL-5-HYDROXY-4-PYRAZOLYL] 1,9 NONANEDIONE AND ITS APPLICATION FOR THE EXTRACTION OF COBALT ( II), NICKEL (II), AND CADMIUM (II) - Ucu Cahyana; Bambang Rusdiarso; Narsito Narsito (Jurnal Riset Sains dan Kimia Terapan, 2017)
Synthesis of 1,9-bis [1-phenyl-3-methyl-5-hydroxy-4- pyrazolol)-1,9-nonanedione (HL-7-LH) and its application for the extraction of cobalt (II), nickel (II), and cadmium (II) have been carried out. The HL-7-LH were prepared by treating a dioxane solution of 1-phenyl-3-methyl-5-pyrazolone (H2PMP) containing calcium hydroxide catalyst with azelaoyl dichloride [ClCO(CH2)7C0C1l Purification of the HL-7-LH obtained were done by mean recrystallization in etanoltoluena (9:1) at 70Â°C. Characterization of the HL-7-LH were done by infrared and nuclear magnetic resonance spectroscopic techniques. The application of the HL-7-LH as extractant in the extraction of cobalt, nickel, and cadmium were performed in chloroform and dichloromethane. It was observed that the effectivity of the extraction increases as the extractant concentration and pH increases. Results show that cobalt, nickel, and cadmium extraction in chloroform wereobtained with the extraction constants (log Keks) = -5,37, -5,44, -5,22 and at dichloromethane were -5,19, - 5,24, and -5,08.Key Word : Synthesis, effectivity of the extraction, the extraction constants